Simultaneous disruption of PRC2 and enhancer function underlies histone H3.3-K27M oncogenic activity in human hindbrain neural stem cells. - Bracken, Adrian; O'Callaghan, Orla (My University, 2021)
Driver mutations in genes encoding histone H3 proteins resulting in p.Lys27Met substitutions (H3-K27M) are frequent in pediatric midline brain tumors. However, the precise mechanisms by which H3-K27M causes tumor initiation remain unclear. Here, we use human hindbrain neural stem cells to model the consequences of H3.3-K27M on the epigenomic landscape in a relevant developmental context. Genome-wide mapping of epitope-tagged histone H3.3 revealed that both the wild type and the K27M mutant incorporate abundantly at pre-existing active enhancers and promoters, and to a lesser extent at Polycomb repressive complex 2 (PRC2)-bound regions. At active enhancers, H3.3-K27M leads to focal H3K27ac loss, decreased chromatin accessibility and reduced transcriptional expression of nearby neurodevelopmental genes. In addition, H3.3-K27M deposition at a subset of PRC2 target genes leads to increased PRC2 and PRC1 binding and augmented transcriptional repression that can be partially reversed by PRC2 inhibitors. Our work suggests that, rather than imposing de novo transcriptional circuits, H3.3-K27M drives tumorigenesis by locking initiating cells in their pre-existing, immature epigenomic state, via disruption of PRC2 and enhancer functions.
PUBLISHED
Keywords: Brain tumors; Stem cells; Neurodevelopment; Cancer; Genes & Society